2016
DOI: 10.1098/rstb.2015.0505
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of pathogenicity islands in helper cos phage interference

Abstract: Staphylococcus aureus pathogenicity islands (SaPIs) are phage satellites that exploit the life cycle of their helper phages for their own benefit. Most SaPIs are packaged by their helper phages using a headful (pac) packaging mechanism. These SaPIs interfere with pac phage reproduction through a variety of strategies, including the redirection of phage capsid assembly to form small capsids, a process that depends on the expression of the SaPI-encoded cpmA and cpmB genes. Another SaPI subfamily is induced and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…Interestingly, the ϕO11 dimeric Dut also induces the SaPIbov1 and SaPIbov5 cycles ( Figure 1A ). Note that SaPIbov5 was also included in these studies because it encodes the same Stl repressor as SaPIbov1, with both islands being induced by the same helper phages ( Carpena et al, 2016 ; Viana et al, 2010 ). Expression of the ϕO11 dimeric Dut (from the P cad promoter in expression vector pCN51) in a SaPIbov1 or SaPIbov5 positive strain demonstrated that this protein is sufficient to induce the SaPI cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the ϕO11 dimeric Dut also induces the SaPIbov1 and SaPIbov5 cycles ( Figure 1A ). Note that SaPIbov5 was also included in these studies because it encodes the same Stl repressor as SaPIbov1, with both islands being induced by the same helper phages ( Carpena et al, 2016 ; Viana et al, 2010 ). Expression of the ϕO11 dimeric Dut (from the P cad promoter in expression vector pCN51) in a SaPIbov1 or SaPIbov5 positive strain demonstrated that this protein is sufficient to induce the SaPI cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, cpmAB genes are present and highly conserved between a large number of SaPIs ( Novick et al, 2010 ). Recently, a different mechanism of capsid size redirection that is not dependent on CpmAB was discovered in a distinct group of SaPIs that are mobilized by cos site phages ( Carpena et al, 2016 ). This example of convergent evolution suggests that size redirection is an important aspect of the long-term survival and establishment of SaPIs in the bacterial population.…”
Section: Discussionmentioning
confidence: 99%
“…They lack any functional terS but have a C-terminal terS remnant, presumably marking one end of the recombinational event. They are packaged by either pac or cos phages using the respective phage TerS's, reportedly in small capsids [32]. The Cap protein homolog (Ccm) causes severe phage interference and seems to be required for the formation of small SaPI particles.…”
Section: Variations On a Theme: The Sapibov5 Familymentioning
confidence: 99%